Distribución, abundancia y preferencias alimenticias del pez sapo Opsanus phobetron (Batrachoididae) en la laguna costera de Chelem, Yucatán, México - Canto-Maza, Walter Gabriel; Vega-Cendejas, María Eugenia (Revista de Biología Tropical, 2018)
Distribution, abundance and alimentary preferences of the fish Opsanus phobetron (Batrachoididae) at the Chelem coastal lagoon, Yucatan, Mexico. Fish are important ecological components in tropical coastal lagoons. In order to evaluate the distribution and feeding preferences of the toadfish Opsanus phobetron in the Chelem Lagoon, Yucatan, Mexico, fish samples were collected using a beach seine in eight stations distributed randomly, from March 2002 to January 2003. The components were analyzed by means of the relative abundance percentage and occurrence frequency. The trophic similarity between ontogenetic stages was determined with the Morisita Index. A total of 221 organisms were collected, with a density and biomass of 92.09 ind/100 m2 and 930.39 g/100 m2 respectively. The highest density and biomass were recorded in the same station. A total of 94 stomach contents were analyzed. Results showed a wide trophic generalization, including 40 alimentary items and great ontogenetic variation: juvenile stages consume preferentially microcrustaceans, while adults mainly feed on fish (96 %). Rev. Biol. Trop. 55 (3-4): 979-988. Epub 2007 December, 28.